Towards Sustainable Development Goals and Environment Stewardship through Geography Education - Singh, Kiran K. (JOURNAL OF INDIAN EDUCATION, 2018)
Distinctiveness of geography as a discipline is revealed through its focus on the study of the earth surface as a world of human. At the time of organisation of knowledge into two broad realms; humanities, social science and sciences, geography could not separate itself due to its inherent nature of performing a role to bridge the human and earthly relationship. The study of geography is by nature ecological in approach and perspective, and creates a bond between the two by studying both, ways of interaction and intervention. Space, time and scale are the critical elements of the discipline which play an important role in the analysis and pursuit of sustainability. This paper deals with the conceptual framework of sustainable development and how geography education plays a role in creating awareness and developing critical thinking about the different components of sustainability at various scales and in different time frames. The paper also brings attention to the core contents or themes of sustainable development which can be seen in the geography curricula in various universities. Sincere attention to content and themes in the curriculum will help to maintain its orientation in the dynamic world scenario. It also discusses the role of geography in transforming learning into environment stewardship.